Effect of waste oyster shell powder content on properties of cement-metakaolin mortar - Yingdi Liao; Xin Wang; Lu Wang; Zhengxing Yin; Bo Da; Da Chen (Case Studies in Construction Materials, 2022)
Considering environmental protection and resources saving, it has been a common approach to apply industrial solid wastes and waste oyster shells (WOS) in cement-based materials. In this study, the percentages of lime (WOS powder) obtained from the calcination WOS to replace ordinary Portland cement (OPC) were 0%, 5%, 8% and 10%. And metakaolin was used as supplementary cementing material. The fresh property, mechanical property, durability of the mortars with different content of WOS powder were investigated. The results indicated that the slump flow decreased with the addition of WOS powder. The mechanical properties and drying shrinkage exhibited an increasing trend with the increase of WOS powder content. The porosity, water absorption coefficient, water permeability coefficient and chloride ion diffusion coefficient decreased with the increase of WOS powder content. Therefore, considering economic and environmental benefit of mortars with different of WOS powder, it is conductive to use 8% calcined WOS powder to replace cement for environmental protection, resource conservation and sustainable development.